The Effects of Rhubarb for the Treatment of Diabetic Nephropathy in Animals: A Systematic Review and Meta-analysis - Zeng, Jing-Yi; Wang, Yu; Miao, Miao; Bao, Xiao-Rong (Frontiers in Pharmacology, 2021)
Background: Rhubarb, also known as Da Huang, is a traditional Chinese medicine. And it was often used as a laxative in the past. Recently, multiple studies have applied rhubarb to treat diabetic nephropathy (DN). Anthraquinones including emodin and rhein have been extracted from rhubarb and used to explore the effective components and possible mechanisms of rhubarb for DN. Evaluating the efficacy of rhubarb may provide a scientific reference for the clinical application of rhubarb for the treatment of DN. Objective: (1)To evaluate the efficacy of rhubarb in the treatment of DN; (2)To identify the most effective ingredient of rhubarb for DN; (3)To explore the specific mechanism of rhubarb in treating DN. Methods: Data sources: Related studies were identified by searching Cochrane Library, Ovid-EMBASE, PubMed, SinoMed, WanFang, VIP, CNKI and other Chinese magazines. Assessment and analysis: SYRCLE’s risk of bias tool for animal studies was used to assess the quality of articles. The meta-analysis was performed in accordance with the Cochrane Handbook for Systematic Reviews of Interventions. Data analysis adopted RevMan 5.3 and STATA 12.0 software. This study was published in the register with PROSPERO, number CRD42020204701. Results: Aggregated data were collected from 27 eligible studies. The results illustrated an intense improvement in the following outcomes in rhubarb-treated animals with DN (P < 0.05): blood glucose, serum creatinine (Scr), blood urea nitrogen (BUN), albumin creatinine ratio (ACR), urine protein (UP), urinary albumin excretion (UAE), renal index (two kidneys weight/body weight, KW/BW), tubulointerstitial injury index (TII), transforming growth factor-beta1 (TGF-β1) mRNA and protein, alpha-smooth muscle actin (α-SMA) protein, E-cadherin (E-cad) protein. Of these, DN animals with rhubarb exhibited a significantly higher level of E-cad protein. In addition, the level of the other outcomes mentioned above decreased significantly. While there was no significant association between the intervention and nephrin protein (P > 0.05). Conclusions: This systematic review and meta-analysis demonstrated that rhubarb has a positive therapeutic effect on animals with DN, which may provide confidence and some theoretical reference for clinical application to a certain extent.